1985
DOI: 10.1177/000348948509400206
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Primary Cancer Risk in Patients with Major Salivary Gland Carcinoma

Abstract: The subsequent primary cancer experience of 498 patients with major salivary gland carcinoma was evaluated using a life-table approach. Expected numbers were generated from two sources. These were population-based tumor registry data and an internal comparison group of randomly selected individually matched patients drawn from the same institution. Compared with either referent group, elevated risk ratios for all cancer sites combined were demonstrated. Risks for subsequent lung cancer were raised but were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Megwalu and Shin showed an elevated risk for second primary cancers in the oral cavity and oropharynx as well as in the salivary glands and kidneys after major salivary gland carcinomas . Similar to our study, several other studies have shown the risk for a second primary breast cancer to be increased, whereas some studies have not . Possible explanations include histological similarities between certain breast and salivary gland carcinomas.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Megwalu and Shin showed an elevated risk for second primary cancers in the oral cavity and oropharynx as well as in the salivary glands and kidneys after major salivary gland carcinomas . Similar to our study, several other studies have shown the risk for a second primary breast cancer to be increased, whereas some studies have not . Possible explanations include histological similarities between certain breast and salivary gland carcinomas.…”
Section: Discussionsupporting
confidence: 89%
“…They showed a significant overall second primary cancer risk of 1.24 and they also had the thyroid among the 3 sites with the highest risk, which is similar to our finding. In the study by Spitz et al, they found an elevated risk for skin cancer among 498 patients with major salivary gland carcinomas, the relative risk being 3.83 (95% CI 1.28‐11.49) in men. In the present series, we also found an increased risk for melanoma and nonmelanoma skin cancers and this risk was higher for men.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is of interest that the standardized incidence ratios remained elevated several years after diagnosis, particularly for melanoma, suggesting either an action on one of the earliest stages of the process of carcinogenesis (19), or the persistence of risk determinants and risk factor exposures. Exposure to UV radiation may also explain, at least in part, the elevated rates of nonHodgkin's lymphomas, assuming that UV radiation causes immunosuppression, although the issue is still open to discussion (5,6,20) The elevated risk of cancer of the salivary glands after squamous cell skin cancer has been observed in other data sets, and is therefore probably real (4,(21)(22)(23). The causes of cancer of salivary glands, apart from a role of radiation (24) which has been associated with squamous cell skin cancer, too, are largely undefined.…”
Section: Discussionmentioning
confidence: 99%